The Educational in Trans-Modern Times: Contributions to the Construction of a Situated Educational Thought [Lo Educativo en Tiempos Trans-Modernos: Aportes Para la Construcción de Un Pensamiento Educativo Situado] - Toro-Arevalo, S (Universidad del Zulia, 2020)
This paper addresses two fundamental aspects in the context of contemporary educational thinking. On the one hand, it enters into characterizing the educational from the Latin American social, theoretical and historic context, describing the configurative components of the process from Freire, Maturana and Ilich, and on the other hand, developing a synthesis of the border proposals of the sciences of cognition through a comprehensive and active educational orientation base located in the context of the ecology of knowledge and the unique cultural mosaic of South America. The methodological basis is fundamentally hermeneutic and epistemological-political. The result is a contribution to the educational discussion revealing, the processes of educational transformation, both at a personal and community level. © 2020, Universidad del Zulia. All rights reserved.